INVESTIGATING LEARNERS’ OBSTACLES IN SECOND LANGUAGE READING COMPREHENSION - Safrudin Sahmadan; Ali Ajam (Universitas Khairun, 2020)
Skill in reading texts written in English as a foreign language constitutes a fundamental element of the establishment of English curriculum in Indonesia. The aim of this article is to investigate and explore the obstacles and difficulties faced by Indonesians in their learning activities which hampering the learners in gaining comprehension, and to view the pedagogy from the broader perspective on the theories of reading process. As the writer found, the learners are lack of language system understanding, lack of reading strategies, poor in recognizing the types of reading comprehension. Therefor, through literary study as the research method, the Â result appeared that the obstacles and problems faced by the Indonesian affected by cultural background, English teaching and learning process, and approaches in teaching and learning.